Results Aimed at Increasing the Efficiency of Information and Communication Technologies in the Process of Teaching Chemistry - Sadokat, Faizulloeva (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
This study aims to evaluate the effectiveness of Information and Communication Technologies (ICT) in enhancing student learning outcomes in chemistry education. Through a mixed-methods approach combining experimental design and qualitative feedback, a range of ICT tools—such as virtual laboratories, interactive simulations, and mobile learning applications—were implemented in classroom settings. The intervention involved pre- and post-testing, as well as surveys and focus group discussions to assess engagement, understanding, and attitudes. Results indicate a statistically significant improvement in students’ academic performance and engagement in the ICT-enhanced group compared to the control group. Students reported higher motivation and better conceptual clarity, particularly in abstract topics. However, challenges such as limited digital access, teacher training gaps, and technical glitches were identified. This research reinforces the transformative potential of ICT in chemistry education while highlighting the need for supportive infrastructure and professional development to ensure sustainable implementation.